Incomplete Infection of Secondarily Infected Potato Plants – an Environment Dependent Underestimated Mechanism in Plant Virology - Bertschinger, Lukas; Bühler, Lukas; Dupuis, Brice; Duffy, Brion; Gessler, Cesare; Forbes, Gregory A.; Keller, Ernst R.; Scheidegger, Urs C.; Struik, Paul C. (Frontiers in Plant Science, 2017)
The common assumption in potato virus epidemiology is that all daughter tubers produced by plants coming from infected mother tubers (secondary infection) will become infected via systemic translocation of the virus during growth. We hypothesize that depending on the prevalent environmental conditions, only a portion of the daughter tubers of a plant that is secondarily infected by viruses may become infected. To test this hypothesis experimental data from standardized field experiments were produced in three contrasting environments at 112, 3280 and 4000 m a.s.l. in Peru during two growing seasons. In these experiments, the percentage of infected daughter tubers produced by seed tubers that were secondarily infected with either potato potexvirus X (PVX), potato Andean mottle comovirus (APMoV), potato potyvirus Y (PVY) (jointly infected with PVX) or potato leafroll luteovirus (PLRV) was determined. Incomplete autoinfection was found in all cases, as the percentage of virus infected daughter tubers harvested from secondarily infected plants was invariably less than 100%, with the lowest percentage of infection being 30%. Increasing altitude tended to decrease autoinfection for all viruses. Therefore, the assumption of complete autoinfection, until now commonly accepted, was rejected, while the hypothesis of environmentally dependent incomplete autoinfection was accepted. The findings help explain the occurrence of traditional seed management practices in the Andes and may help to develop locally-adapted seed systems in environments of the world that have no steady access to healthy seed tubers coming from a formally certified seed system. The results obtained almost three decades ago are discussed in light of most recent knowledge on epigenetic regulation of host plant – virus interactions which allow for speculating about the underlying biological principles of the incomplete autoinfection. A research roadmap is proposed for achieving explicit experimental proof for the epigenetic regulation of incomplete autoinfection in the pathosystem under study.